Analisis Pembagian Nisbah Dalam Akad Mudharabah Antara Shahibulmal Dengan Mudharib Ditinjau dari Aspek Hukum dan Aspek Ekonomi Syariah di Bank BNI Kantor Cabang Pembantu Boyolali - Faizal Dewantara (STIS DAFA MATARAM, 2020)
Analysis of the distribution of the ratio in the Mudharabah agreement between Shahibul Mal and Mudharib in terms of legal and economic aspects of sharia at Bank Bni, Boyolali Sub-Branch Office, is in accordance with the regulations according to Islam. PT. Bank Negara Indonesia (BNI) Syariah is a company engaged in banking whose activities are to provide services to the community, both services and other banking products. BNI Syariah was formed independently through the Internal Project Team. The pattern used by PT. Bank Negara Indonesia (Persero) tbk. Sharia to enter into the Islamic banking market is a dual banking system. Mudharabah agreement is an agreement for financing or investing funds from the owner of funds (shahibul maal) to fund management (mudharib) to carry out certain business activities that are in accordance with sharia, with the sharing of business results between the two parties based on a ratio that has been previously agreed. It was concluded that the distribution of the ratio carried out by shahibul maal with mudharib in the mudharabah agreement at the BNI syariah bank Boyolali sub-branch office in funding (deposits) was in accordance with Islamic law and the distribution of the Nisbah in the mudharabah contract at Bank BNI Syariah Boyolali Sub-Branch Office was not found elements that containing Maisir, Gharar and usury in the implementation of the contract between Islamic banking and customers. The contract in the implementation of the agreement has been known and agreed upon at the beginning of both parties. The agreement is in accordance with the regulations by the DSN-MUI and Islamic law.